2002
DOI: 10.1093/genetics/160.4.1749
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Filamentous Growth of Candida albicans Is Promoted by Czf1p-Dependent Relief of Efg1p-Mediated Repression

Abstract: Filamentation of Candida albicans occurs in response to many environmental cues. During growth within matrix, Efg1p represses filamentation and Czf1p relieves this repression. We propose that Czf1p interacts with Efg1p, altering its function. The complex regulation of filamentation may reflect the versatility of C. albicans as a pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In contrast to its widely described role as a positive regulator of filamentation, Efg1 also acts as a suppressor of filamentation under embedded and hypoxic conditions, as deletion of EFG1 under these conditions causes an increase in filamentation ( Giusani et al., 2002 ; Doedt et al., 2004 ; Mulhern et al., 2006 ). The increase in filamentation observed in efg1 Δ/ efg1 Δ mutants under hypoxic conditions occurs at temperatures <37°C suggesting the repressive effects of Efg1 are temperature dependent ( Setiadi et al., 2006 ).…”
Section: Role Of Efg1 In Filamentation and Morphogenesismentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast to its widely described role as a positive regulator of filamentation, Efg1 also acts as a suppressor of filamentation under embedded and hypoxic conditions, as deletion of EFG1 under these conditions causes an increase in filamentation ( Giusani et al., 2002 ; Doedt et al., 2004 ; Mulhern et al., 2006 ). The increase in filamentation observed in efg1 Δ/ efg1 Δ mutants under hypoxic conditions occurs at temperatures <37°C suggesting the repressive effects of Efg1 are temperature dependent ( Setiadi et al., 2006 ).…”
Section: Role Of Efg1 In Filamentation and Morphogenesismentioning
confidence: 92%
“…The effects observed in mutations to regions outside of the DNA binding region may be due to changes in either protein interaction regions and/or phosphorylation sites. Yeast two-hybrid studies have shown that Efg1 is capable of interacting with several proteins including Czf1, Flo8, and members of the NuA4 histone acetyltransferase complex ( Giusani et al., 2002 ; Cao et al., 2006 ; Lu et al., 2008 ; Noffz et al., 2008 ). These same studies demonstrated that the typical protein-protein interaction site, the APSES structure, is not required for Efg1 protein-protein interactions with Czf1 or Flo8 ( Cao et al., 2006 ; Noffz et al., 2008 ).…”
Section: Efg1 Structure and Dna Binding Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Under hypoxia, it acts as a repressor at temperatures ≤ 35 • C, while under normoxia (normal oxygen level), Efg1 is a strong inducer of hyphal formation [48]. efg1∆/∆ mutants displayed hyperfilamentous growth at temperatures ≤ 35 • C during hypoxic growth on agar surface or during embedment in agar but not during growth in liquid media [48,49]. In contrast, Ace2 is essential for hyphal morphogenesis under hypoxia while being dispensable under normoxia [50,51].…”
Section: Hypoxia (Low Oxygen)mentioning
confidence: 99%
“…Czf1 is a zinc cluster DNA binding protein that is required for WT filamentation in cells grown in contact with agar but not under liquid growth conditions ( 21 , 22 ). Recently, Czf1 has been shown to be a regulator of cell wall architecture and integrity and is also required for basal levels of caspofungin tolerance ( 23 ).…”
Section: Resultsmentioning
confidence: 99%